My life as a Hindu - Bradley, Fleur (Bradley, Fleur. How the world worships., 2022)
A girl in America and a boy in India describe the origins, beliefs, practices, sacred texts, and celebrations of Hinduism. Includes color photographs, a glossary, a timeline of major events, an activity, and further resources.